2016
DOI: 10.1080/0886022x.2016.1193874
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines, adipocytokines and inflammatory markers in patients on continuous ambulatory peritoneal dialysis and hemodialysis

Abstract: We can conclude that cytokine production is more obvious in HD process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Supporting this, we found higher serum levels among patients receiving pre-transplant hemodialysis compared with those on peritoneal dialysis. Some authors have observed differences in concentrations of proinflammatory cytokines (such as tumor necrosis factorα or IL-6) according to the dialysis modality,51 although discordant results have been also reported 52. In our…”
supporting
confidence: 63%
See 1 more Smart Citation
“…Supporting this, we found higher serum levels among patients receiving pre-transplant hemodialysis compared with those on peritoneal dialysis. Some authors have observed differences in concentrations of proinflammatory cytokines (such as tumor necrosis factorα or IL-6) according to the dialysis modality,51 although discordant results have been also reported 52. In our…”
supporting
confidence: 63%
“…Supporting this, we found higher serum levels among patients receiving pre‐transplant hemodialysis compared with those on peritoneal dialysis. Some authors have observed differences in concentrations of proinflammatory cytokines (such as tumor necrosis factor‐α or IL‐6) according to the dialysis modality, although discordant results have been also reported . In our opinion, these lines of reasoning (elevated hepcidin‐25 levels due to either iron overload or maintained inflammatory response) should be regarded as complementary rather than mutually exclusive, since both conditions may synergistically interact to increase the infection risk.…”
Section: Discussionmentioning
confidence: 87%
“…Also, healthy aging adults have higher circulating levels of cytokines including IL-6, IL-8, IL-10, and TNF-α [53]. Several of these circulating cytokines including TNF-α and IL-6 are higher in patients with chronic renal failure [54,55] and this can occur even in the absence of aging. It is conceivable that indicating higher levels of circulating cytokines in aging can affect kidney function.…”
Section: Immune Systemmentioning
confidence: 99%
“…The use of the peritoneal membrane in PD may remove inflammation-inducing substances much more effectively compared to the dialyzer membrane in hemodialysis. 22) Indeed, Oncel, et al demonstrated that the serum TNF-α and IL-6 levels of patients on continuous ambulatory PD were significantly lower than with hemodialysis. 22) In addition, the use of an icodextrin-containing PD solution may have had favorable effects on the uremic milieu and metabolic control and thus, the cardiac hemodynamics in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…22) Indeed, Oncel, et al demonstrated that the serum TNF-α and IL-6 levels of patients on continuous ambulatory PD were significantly lower than with hemodialysis. 22) In addition, the use of an icodextrin-containing PD solution may have had favorable effects on the uremic milieu and metabolic control and thus, the cardiac hemodynamics in the present study. 12) Meanwhile, it should be noted that patients with poor comprehensive understanding and management abilities for daily PD procedure are not suitable for home-based chronic PD.…”
Section: Discussionmentioning
confidence: 99%